The stochastic Differential Equations Model for the Spread of Viral Hepatitis and Immune Response - Kareem, Ahmed M. (Iraqi Journal of Science, 2025)
The investigate of the dynamic behavior of viral hepatitis to stop the illness from spreading have been studied in this paper. A novel stochastic mathematical model was created in order to conduct the study. We prove this proposed model has a positive unique solution. By looking up the basic reproduction number, we also demonstrated the requirements that must be fulfilled for the injured person to heal. If   it means that the liver will get rid of the virus and heal the infected person. While if  , the infection grows and the disease can invade all liver cells. Computer simulations have also been used to illustrate these findings.